The Use of Request Strategy in Leave the World Behind Movie - Khairunisa, Naila Putri; Aprilia, Intan Ika; Rosalinah, Yanti (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The title of this study is